Correlates of microalbuminuria in hypertensive patients of a tertiary care teaching hospital of Central India - Tagore, Praveen Kumar; Gupta, Archana; Kumar, Dewesh; Yadav, Moorat Singh (International Journal of Research in Medical Sciences, 2017)
Background: Although the prevalence of hypertension is high in India, the relationship between micro-albuminuria and target organ damage in hypertension is not well studied. Hence this study aims to study the prevalence of micro-albuminuria in patients of hypertension and its correlation with other cardiovascular risk factors. Methods: This cross-sectional study was done in 112 essential hypertension non-diabetic patients presented at a tertiary care hospital of Madhya Pradesh, India who fulfilled inclusion criteria and exclusion criteria during a calendar year. The diagnosis of essential hypertension was made by the study physician after complete medical history, physical examination and routine biochemical analysis of blood and urine. The data was analysed using SPSS version 20 and Mann Whitney U and Chi-square test was used for quantitative and qualitative data respectively. Results: The total number of patients having micro-albuminuria was 26 and the prevalence came out to be 23.21%. The mean age of micro-albuminuric patients was less compared to non-microalbuminuric patients (p<0.05). The systolic, diastolic blood pressure and cholesterol levels were found to be higher but was statistically insignificant whereas body mass index (BMI) and duration of disease was statistically higher (p<0.05) amongst the cases having micro-albumin in their urine. Conclusions: The prevalence of micro-albuminuria increases with the increase in duration, stages /severity of hypertension. Micro-albuminuria may be considered as a marker of adverse cardiovascular risk profile such as LVH and hyperlipidemia. High BMI, smoking and advanced stages of retinopathy are also the risk factors of micro-albuminuria.